Perspectives of the Farmers on Collection of Vegetables at Dambulla Dedicated Economic Center in Sri Lanka (International Journal of Scientific Research and Management (IJSRM), 2022)
Agricultural products move through several channels before reaching the final consumers. The collection process of vegetable must be effective and efficient to avoid losses in the supply chain of vegetables. The Dambulla Dedicated Economic Center (DDEC) is considered as the main hub of vegetable and fruit distribution in Sri Lanka. The objective of this research is to analyze the role of DDEC in collection of vegetables in Sri Lanka and explore whether the center meets the best practices of vegetable collection. Transportation, packing and packaging, role of middlemen, and training and knowledge on vegetable collection process were reviewed. Data were collected using a semi structured questioner from 70 farmers linked to the DDEC. High level of quality degradation, poor packing and packaging, lack of knowledge and training on collection, and inefficient role of middlemen were identified as the main issues related to the vegetable collection process of DDEC in Sri Lanka.